2017
DOI: 10.1136/svn-2016-000049
|View full text |Cite
|
Sign up to set email alerts
|

Association between large artery atherosclerosis and cerebral microbleeds: a systematic review and meta-analysis

Abstract: ObjectiveThe aim of this systematic review and meta-analysis was to provide evidence that biomarkers of large artery atherosclerosis, including arterial stenosis and greater carotid intima-media thickness (cIMT), may serve as clinical markers of subclinical haemorrhage-prone cerebral small vessel disease, reflected by cerebral microbleeds (CMBs).MethodsWe searched PubMed, MEDLINE, Web of Science, EMBASE and the Cochrane Library to identify relevant studies published before 1 July 2016. The association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
0
3
1
1
Order By: Relevance
“…However, the post hoc analytic approach may result in false-positive findings, and the mechanism underlying the association between microbleeds or PVS and bleeding events needs further investigation. Previous meta-analysis suggested that ICAS may be associated with microbleeds,26 our investigation did not find significant interaction between CSVD burden and ICAS, while CSVD may be associated with haemorrhagic events independently.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the post hoc analytic approach may result in false-positive findings, and the mechanism underlying the association between microbleeds or PVS and bleeding events needs further investigation. Previous meta-analysis suggested that ICAS may be associated with microbleeds,26 our investigation did not find significant interaction between CSVD burden and ICAS, while CSVD may be associated with haemorrhagic events independently.…”
Section: Discussioncontrasting
confidence: 75%
“…The presence of cerebral microbleeds is considered a strong predictor of future stroke, particularly haemorrhagic stroke. Ding et al 27 performed a systematic review and meta-analysis and found that there is a relationship between large artery atherosclerosis and cerebral microbleeds. Isolated medial layer thickness reflects not only early atherosclerosis but also nonatherosclerotic compensatory remodelling with large medial hypertrophy as a result of smooth muscle cell hyperplasia and fibrocellular hypertrophy 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, dysfunction of endothelial cells is a critical event in the pathological process of atherosclerosis, which leads to apoptosis of vascular arterial walls, atherogenesis, aortic plaque and macrophage infiltration (5)(6)(7). In addition, atherosclerosis is generally regarded as a lipid-induced chronic inflammation in the vessel wall, which leads to inflammatory lesions and apoptosis of endothelial cells (8)(9)(10). Thus, elucidating the possible mechanisms underlying the inflammatory process and apoptotic signal molecular pathways involved in the pathology of atherosclerosis are crucial to understand the occurrence and development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%